Marketingowe problemy procesów integracyjnych - kontekst konkurencji i postrzegania wartości - Styś, Aniela (Problems of Marketing in Terms of Integration Process - Context of Competition and Value Perception, 2007)
The author pays attention to marketing problems connected with the European integration process and unequal development as a factor that has impact on character and the meaning and also threats connected with less developed economies' competitiveness. The article presents survey findings essential for creating company competitiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 41-52